ORAL TRADITION: FOLK TALES AND ITS SIGNIFICANCE IN UNDERSTANDING THE KOKBOROK SPEAKING SOCIETY OF TRIPURA - Debbarma, Sukhendu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Early societies since time immemorial relied on oral tradition to preserve record of their past in the absence of written histories. Oral tradition has played a crucial role in preserving the cultural heritage and history of societies, especially those with non-literate backgrounds. In the context of the Kokborok speaking community of Tripura, folktales serve as significant oral sources that transmit cultural values, social norms, and historical narratives from one generation to the next. This paper highlights the significance of folktales in understanding the Kokborok speaking society, focusing on three notable folktales: Chethuang, Nwai, and Kuchuk Kherengbar. The Chethuang folktale, centeres around a brother and sister’s taboo love, imparts a moral lesson about the social prohibition of incest and the natural consequences of such actions. The tale of Nwai highlights the mistreatment of a step-daughter by her stepmother, reflecting on the dynamics of family relationships and the social challenges faced by women in traditional societies. The Kuchuk Kherengbar folktale, which revolves around a forbidden love between a boy and a girl from historically separated families, emphasizes themes of societal taboo and natural repercussions, symbolized through the transformation of the lovers into animals. These folktales not only offer understanding into the beliefs, customs, and societal norms of the Kokborok speaking community but also demonstrate the broader role of oral traditions in shaping and preserving collective cultural identity. By analyzing these narratives, the paper emphasizes the significance of folklore in stimulating a sense of community, identity, and continuity in the face of changing societal structures and challenges. Through these folktales, the Kokborok speaking community has maintained a strong connection to its cultural roots, strengthening moral values and societal principles across generations.